FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KURANGNYA MINAT IBU MEMBERIKAN ASI EKSKLUSIF PADA BAYINYA DI BIDAN PRAKTEK MANDIRI HERASDIANA PALEMBANG TAHUN 2022 - Khoiriah, Annisa; Nelly Mariyam (Jurnal Kesehatan dan Pembangunan, 2024)
Breast milk is the best and only food needed by babies and contains many nutrients. Exclusive breastfeeding is breastfeeding without complementary foods and drinks (including orange juice, honey, sugar water), which starts from the time the baby is born until the age of 6 months. Coverage of mothers providing exclusive breastfeeding in South Sumatra and in every district is still below the Minimum Service Standards (SPM), namely 80%. This study aims to determine the factors associated with mothers' lack of interest in providing exclusive breastfeeding to their babies at BPM Herasdiana Palembang in 2022. This type of research is an analytical survey with a cross-sectional approach. The sample in this study was mothers who had babies aged 7-12 months. The sample was taken using an accidental sampling technique of 51 respondents. Data analysis using the chi square test showed that the variables of maternal knowledge (p = 0.004) and husband's support (p = 0.004) had a significant relationship with exclusive breastfeeding, while maternal employment (p = 1.000) had no significant relationship with exclusive breastfeeding. It is hoped that the results of this research will be useful for breastfeeding mothers, researchers and health workers at community health centers so that they can provide information and education to mothers about the benefits and importance of exclusive breastfeeding.